Pengaruh Suhu Dekoksi Terhadap Kadar Kurkumin Dan Aktivitas Antioksidan Pada Rimpang Temulawak (Curcuma Zanthorrhiza) - Baiq Desy Ratnasari; Diah Miftahul Aini (Journal of Pharmaceutical and Health Research, 2023)
One of the medicinal plants that are widely used and available is Curcuma xanthorrhiza. In a daily consumption, C. xanthorrhiza is processed into herbal drinks through a decoction process. However, many biological activities of a plant may be sensitive to the temperature due. Thus, this study is analyzing the effect of temperature on one of the major compounds of C. xanthorrhiza, namely curcumin, along with its antioxidant activity. This research was conducted to obtain the optimum temperature for C. xanthorrhiza processing in order to standardize it as phytopharmaca product. The results showed that a temperature of 100oC was the optimal temperature for the decoction with an extraction rate of 8 ppm and an antioxidant activity of 165 ppm. The curcumin content seems not too sensitive to temperature when seen from the levels obtained at 70oC, 90oC and 100oC which are both 8 ppm. On the other hand, the antioxidant activity of C. xanthorrhiza at temperatures below 100oC has no significant activity which indicates the effect of temperature on its antioxidant activity. The curcumin standard itself has an IC50 of 120 ppm while the IC50 of vitamin C is 24.3 ppm. As it seen from the insignificant antioxidant activity of the decoction extract below 100oC, it is possible that there are other compounds besides curcumin which are extracted only at 100oC which has the agonist effect on the antioxidant activity